Space organization in Perak Malay traditional house analysis of space organization on Perak Malay traditional house / Othman Mohd Nor ... [et al.] - Mohd Nor, Othman; Misnat, Nordin; Mohd Isa, Haryati; Abd Karim, Norashikin (Universiti Teknologi MARA, Perak, 2021)
The Perak Malay Traditional houses are one of the relics that should be appreciated due to their space organization uniqueness which is not present in today's modern houses. The study of the house's space organization should highly be given attention for future generations to discern. The issue is there is minimal approach on appreciating the space organization and there is even no concern of its benefits if applied in the construction of modern houses today. Indeed, in an orientation before the construction of a residential house, the role of the environment including culture, way of life, especially the occupants of the residence are taken care of by a craftsman. Discussion between the host and the craftsman is an important aspect before the residence is established. Space requirements are the most in the architecture of a traditional Malay house, a space was born as a result of the activities of society, by gender requirements in addition to the comfort of concern with the residential environment. Space requirements are common in almost every traditional Malay house in Malaysia but there are differences in orientation, climate, environment and local culture that trigger the use of a space. The purpose of this study is to pass knowledge to the future generation in order to appreciate the relics house. For that, the objectives of this research is to analyse the spatial organization design and architecture of a traditional Malay house with Perak state based on the space functional diversity through research on the role of space during performance of activities. This paper employs a qualitative research adapting the observation on-surrounding and the house's interior space. Besides, sketches on house spatial pattern, joinery detailing and joinery construction were some of the approaches that have been applied to obtain the data. To strengthen data acquisition, interviews with target groups like village heads or local house carpenters were made. The data were analysed and the sketches were illustrated in diagrams to interpret the pattern of findings. The results strengthened the characteristics of the interior spatial organization for Perak house traditionally do influence the environment, society, cultural customs, beliefs and religions.